A study of cardiovascular abnormalities in newly diagnosed HIV infected children (International Journal of Biomedical and Advance Research, 2018)
Background: Children infected with HIV may develop a wide range of cardiovascular abnormalities, some of which are known to be associated with poor survival. With advances in the management of HIV patients, not only survival has increased but manifestations of late stage HIV infection are encountered more often including cardiovascular complications. Aims: The present study was undertaken to determine the prevalence and nature of cardiovascular abnormalities in newly diagnosed HIV infected children. Method: In this prospective, observational study, total 86 newly diagnosed HIV infected children, having age below 15 years and who were attending the PCOE at tertiary care institute were included in the study. All these recruited patients were subjected to chest radiograph, electrocardiography and 2D- echocardiography. Results: There were six (7%) children with abnormal cardiovascular examination in form of tachycardia, tachypnea, increased precordial activity or murmur. Abnormal findings on chest radiograph were seen in 27 patients. Eight patients had right ventricular strain pattern and 3 patients had incomplete bundle branch block on electrocardiograph. On 2D echocardiography only 2 patients had thin rim of pericardial effusion. There was no significant correlation between these findings and clinical and immunological stage of patients. In patients with low CD4 counts or advanced stage there are higher chances of detecting a cardiovascular problem. Conclusion: The study concluded that it is not cost effective to investigate for cardiovascular abnormalities in all newly diagnosed children at the onset. It can be done based on clinical examination, CD4 counts, stage of patients, and on follow up.